A new silent germline mutation of the TSH receptor: Coexpression in a hyperthyroid family member with a second activating somatic mutation - GÖZÜ, HÜLYA; ÖNEŞ, TUNÇ (MARY ANN LIEBERT, INC, 2008)
Background: Up to date, three thyroid-stimulating hormone receptor (TSHR) germline variants have been reported for which no functional consequences have been detected by in vitro characterizations. However, familial nonautoimmune hyperthyroidism and hot nodules are clearly associated with constitutively activating TSHR germline mutations. We describe a family with a new TSHR germline mutation that is associated with euthyroidism in 13 family members and hyperthyroidism in 1 family member. Methods: Mutation analysis of the TSHR gene was performed by denaturing gradient gel electrophoresis. TSHR constructs were characterized by determination of cell surface expression, 3'-5'- cyclic adenosine monophosphate ( cAMP) accumulation, and constitutive cAMP activity. Results: A novel TSHR germline mutation ( N372T) was found in a man who presented with thyrotoxicosis. The mutation was also detected in 13 family members, all of whom were euthyroid. Interestingly, an additional constitutively active somatic mutation ( S281N) was identified on the second parental TSHR allele of the hyperthyroid index patient. Linear regression analysis showed a lack of constitutive activity for N372T. Moreover, coexpression studies of N372T with S281N did not reveal any evidence for a functional influence of N372T on the constitutively active mutation ( CAM). Conclusions: N372T is unlikely to cause altered thyroid function. This is consistent with the finding that only the index patient with the additional somatic mutation S281N was hyperthyroid.
Keywords: STIMULATING HORMONE-RECEPTOR; HUMAN THYROTROPIN RECEPTOR; AUTOSOMAL-DOMINANT HYPERTHYROIDISM; NON-AUTOIMMUNE HYPERTHYROIDISM; TOXIC THYROID-NODULES; NONAUTOIMMUNE HYPERTHYROIDISM; CONGENITAL HYPERTHYROIDISM; EXTRACELLULAR DOMAIN; FUNCTIONAL-CHARACTERISTICS; CONSTITUTIVE ACTIVATION